2009
DOI: 10.1007/s00449-009-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Alginate immobilization of recombinant Escherichia coli whole cells harboring l-arabinose isomerase for l-ribulose production

Abstract: Recombinant Escherichia coli whole cells harboring Bacillus licheniformis L-arabinose isomerase (BLAI) were immobilized with alginate. The operational conditions for immobilization were optimized with response surface methodology. Optimal alginate concentration, Ca(2+) concentration, and cell mass loading were 1.8% (w/v), 0.1 M, and 44.5 g L(-1), respectively. The interactions between Ca(2+) concentration, alginate concentration, and initial cell mass were significant. After immobilization of BLAI, cross-linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 33 publications
3
22
0
1
Order By: Relevance
“…Meanwhile, immobilized esterase in non-coated alginate beads displayed a minor possibility of reuse with significant loss of original enzymatic activity after three subsequent cycles. Similar results was observed with other immobilized enzymes and reported that soft surface of non-coated beads compare to silicate coated alginate beads may be the reason for leakage of enzyme from the beads that results in loss of enzymatic activity after subsequent cycle in noncoated Ca-alginate beads [16,17]. The results prove that coating alginate beads with silicate is important for utilization of esterase in continuous processes.…”
Section: Optimum Conditions For Esterase Immobilizationsupporting
confidence: 77%
See 3 more Smart Citations
“…Meanwhile, immobilized esterase in non-coated alginate beads displayed a minor possibility of reuse with significant loss of original enzymatic activity after three subsequent cycles. Similar results was observed with other immobilized enzymes and reported that soft surface of non-coated beads compare to silicate coated alginate beads may be the reason for leakage of enzyme from the beads that results in loss of enzymatic activity after subsequent cycle in noncoated Ca-alginate beads [16,17]. The results prove that coating alginate beads with silicate is important for utilization of esterase in continuous processes.…”
Section: Optimum Conditions For Esterase Immobilizationsupporting
confidence: 77%
“…In contrast, non-coated alginate beads surface have had some pores which may be the reason of enzyme leakage displaying lower enzymatic activity. Other researchers have also reported that surface modification of immobilized enzyme may prevent the leakage and keep the activity of enzyme by forming a physical barrier [16,17,20].…”
Section: Optimum Conditions For Esterase Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, immobilization has inherent advantages compared to the free cells including enhanced stability of the system, easy separation of cells, minimizing or eliminating the cell contaminations in the products, convenient recovery and re-use of cells which enable their frequent use in the process [5]. Magnetic separation is a promising technology in the support systems for immobilization, since the rapid separation and easy recovery of immobilized cells could be reached in an external magnetic field, and the capital and operation costs could also be reduced [6].…”
Section: Introductionmentioning
confidence: 99%